(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Pure sulphamic acid (SA) and L-phenylalanine added sulphamic acid (LPASA) were grown by slow evaporation technique. Structural analysis revealed that the orthorhombic crystal structure was retained for both the grown crystals and the crystallinity was improved upon the addition of L-phenylalanine. The vibrational analysis of both FTIR and Raman exhibited all the vibrational frequencies related to the stretching, deformation, and zwitterion nature of the sulphamic acid crystal. All the vibrational modes proved that the addition of L-phenylalanine enhanced crystalline nature. The elemental analysis confirmed the presence of all constituent elements and the surface morphological study affirmed the improvement in classification of crystal grains. The transmittance was raised to 92%. Moreover, the hardness of the crystal was enhanced. The thermal stability and hardness of the SA crystal was intensified with the addition of L-phenylalanine. The photoluminescence studies revealed that the blue emission intensity was increased on addition of L-phenylalanine. Therefore L-phenylalanine was considered as a good additive for sulphamic acid to improve the crystalline nature as well as the thermal and mechanical stability of the crystal. Addition of L-Phenylalanine with the pure SA enhanced the antibacterial activity was enhanced, which will be proficient in killing pathogenic bacteria. Moreover, the blue emission intensity was enhanced upon L-phenylalanine addition. Hence this material may be useful for application in blue emission LED devices.